2017
DOI: 10.1007/s00432-017-2370-1
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA UCA1 regulates the expression of Snail2 by miR-203 to promote hepatocellular carcinoma progression

Abstract: Our results identified that UCA1/miR-203/Snail2 pathway might involve in HCC progression. Inhibition of UCA1 acted as a promising therapeutic target for HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 25 publications
1
80
0
Order By: Relevance
“…Slug has been confirmed as the downstream effector of TGF-b signaling pathway; here, we indicated that lncRNA UCA1 served as the downstream effector of TGF-b and the upstream effector of Slug, respectively, which is consistent with recent studies in other cancers [14,19,20]. Thus, we wonder whether the TGF-b-UCA1-Slug regulatory axis is a common phenomenon in cancers.…”
Section: Discussionsupporting
confidence: 89%
“…Slug has been confirmed as the downstream effector of TGF-b signaling pathway; here, we indicated that lncRNA UCA1 served as the downstream effector of TGF-b and the upstream effector of Slug, respectively, which is consistent with recent studies in other cancers [14,19,20]. Thus, we wonder whether the TGF-b-UCA1-Slug regulatory axis is a common phenomenon in cancers.…”
Section: Discussionsupporting
confidence: 89%
“…As a novel regulatory mechanism, lncRNAs act as an endogenous ceRNA or sponge for miRNAs to regulate the degradation of miRNA targets . For example, UCA1 overexpression promoted epithelial‐mesenchymal transition (EMT) in hepatocellular carcinoma via effectively sponging miR‐203 and thereby activating the expression of transcription factor Snail2, a target of miR‐203 . UCA1 upregulation enhanced tamoxifen resistance in breast cancer cells through a miR‐18a‐HIF1α feedback loop .…”
Section: Discussionmentioning
confidence: 99%
“…Based on its their reported functionality, demonstrated target genes and expression pattern during chick development (Darnell et al, 2006), we further focused on miR-203 for in depth analysis. Importantly, miR-203 has been described to act as tumor suppressor (Benaich et al, 2014, Miao et al, 2014, Zhu et al, 2013b), that directly regulates Snail2 expression (Gao et al, 2017, Shi et al, 2015, Zhang et al, 2015, Xiao et al, 2017), whose epigenetic repression causes metastasis in several tumor cells including NCC-derived melanoma (Boldrup et al, 2012, Boll et al, 2013, Chen et al, 2012, Chiang et al, 2011, Ding et al, 2013, Furuta et al, 2010, Huang et al, 2014, Ju et al, 2014, Moes et al, 2012, Zhang et al, 2014, Zhao et al, 2013, Bu and Yang, 2014, Lohcharoenkal et al, 2018). Moreover, the mature miR-203 sequence is highly conserved throughout vertebrates including the basal lamprey (Fig.…”
Section: Resultsmentioning
confidence: 99%